Оценка рациональности форм укладки совмещенных обмоток в торцевой части полифункционального электромеханического преобразователя - Заблодский, Николай Николаевич; Лупанов, Андрей Викторович; Грицюк, Владимир Юрьевич (НТУ "ХПИ", 2010)
Предложена конструктивная компоновка совмещенных обмоток погружного электромеханического преобразователя в торцевой зоне внешнего статора. Рассмотрена картина магнитного поля при использовании разных профилей пазов и разной глубине их расположения на статоре, рассчитаны основного магнитного потока и потока пазового рассеяния в торцевой части кольцевой обмотки.

Structural arrangement of combined windings of a submersible electromechanical converter in the front area of an external stator is introduced. Patterns of magnetic field for different types of slots and different depth of their location on the stator are considered, the basic magnetic flux and slot leakage flux in the front part of circular winding calculated.
Rationality estimation of combined windings structural arrangement in front area of a polifunctional electromechanical converter
Keywords: обмотки асинхронных машин; прямоугольный паз; магнитные потоки рассеяния; основные магнитные потоки; submersible electromechanical converter; dispersion flux; circular winding; structural arrangement